2021
DOI: 10.3390/cancers13071634
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Parameters as Biomarkers of Response to Immunotherapy and Prognosis in Non-Small Cell Lung Cancer (NSCLC): A Real World Experience

Abstract: Immune-checkpoint inhibitors (ICIs) have been proven to have great efficacy in non-small cell lung cancer (NSCLC) as single agents or in combination therapy, being capable to induce deep and durable remission. However, severe adverse events may occur and about 40% of patients do not benefit from the treatment. Predictive factors of response to ICIs are needed in order to customize treatment. The aim of this study is to evaluate the correlation between quantitative positron emission tomography (PET) parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…In a previous study by our group comparing the first response assessment to Nivolumab using CT and FDG PETbased criteria in the same cohort of patients, FDG imaging maintained a prognostic value even in patients classified as PD based on CT [28]. This prognostic value was also observed when tumor burden parameters (i.e., MTV and TLG) were applied [22,29,30]. Similarly, in previous studies on the use of PET-based response in melanoma patients receiving ICIs, it was demonstrated that as much as half of patients showing residual disease on CT have negative FDG-PET scans [31][32][33][34].…”
Section: Discussionmentioning
confidence: 67%
“…In a previous study by our group comparing the first response assessment to Nivolumab using CT and FDG PETbased criteria in the same cohort of patients, FDG imaging maintained a prognostic value even in patients classified as PD based on CT [28]. This prognostic value was also observed when tumor burden parameters (i.e., MTV and TLG) were applied [22,29,30]. Similarly, in previous studies on the use of PET-based response in melanoma patients receiving ICIs, it was demonstrated that as much as half of patients showing residual disease on CT have negative FDG-PET scans [31][32][33][34].…”
Section: Discussionmentioning
confidence: 67%
“…However, volume-based PET parameters were extracted. In this context, a bicentric Italian study performed an analysis in a bigger cohort of 92 patients, demonstrating that those with PD had higher MTV median values compared to those with controlled disease [ 17 ]. Similarly, Polverani and colleagues observed a significant association of MTV and TLG of the primary lesions with PD, since lower MTV and TLG values were associated with non-PD status [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, new semiquantitative parameters, namely metabolic tumor volume (MTV) and total lesion glycolysis (TLG) rate, have been studied to evaluate the predictive and prognostic value of the metabolic tumor burden at baseline [18F]FDG PET/CT. Many of these studies have shown that new PET metabolic parameters are better in predicting prognosis in early and advanced NSCLC and SCLC patients than conventional PET parameters (SUVmax or SUVmean) [ 178 , 179 ].…”
Section: In Vivo Biomarkers For Immunotherapy: Molecular Imagingmentioning
confidence: 99%